Design and Simulation of Graphene Based Antenna for Radiation Pattern - Chandra S.; Dwivedi S. (My University, 2025)
The present paper has been proposed to solve the problem of getting radiation pattern reconfiguration in a single antenna that fulfils the requirement of multifunctional system with better performance with the confined volume at higher frequency. At high frequency (THz), the communication system comprise of higher transmission data rate and the low transmitting power with reliable wireless systems. This paper represents the design and analysis of monolayer graphene based reconfigurable array antenna (patches are 1×4 array on polyimide substrate) at terahertz (THz) band for three reconfiguration frequency, radiation pattern. The results obtained show that the designed antenna resonates at frequency, 0.71 THz with 10.17 dB gain, directivity, 12.69 dB as well as with 60% efficiency, and the reconfiguration in frequency is achieved from frequency ranges, 0.64 THz-0.74 THz, reconfiguration in radiation pattern is achieved 82°-115° and reconfiguration in polarization is achieved as linear, right hand circular polarization and left hand circular polarization using commercial software CST microwave studio. © 2021 IEEE.